Penggunaan Kontrasepsi Oral dan Risiko Obesitas Pada Wanita Usia Subur - Iqlima Den Firza; Nurmainah Nurmainah (Fakultas Farmasi Universitas Setia Budi, 2021)
Oral contraception is a method that can be used to support family planning programs. However, there are some side effects that can be caused by the use of oral contraceptives, one of which is weight gain, which is a major risk factor for obesity. Obesity is known as a factor in the development of hypertension and diabetes mellitus. This research aimed to analyze the correlation between duration of use and type of oral contraception that is alleged to have a risk of obesity. This study using an observational method with an analytic cross-sectional study design. The data was taken based on acceptors’ medical records for the period January 2018-March 2019. Data collection techniques using purposive sampling with samples that comply with the inclusion and exclusion criteria is 68 samples. The results showed that the longer used of oral contraception, the higher the risk of obesity in oral contraception acceptors (p = 0.001; OR = 20.7; CI95% = 4.87-87.95). Using the type of combined oral contraceptives also has a higher risk of obesity in oral contraception acceptors (p = 0.011; OR = 10.2; CI95% = 1.25-82.87). The conclusion of this study that duration of use and type of oral contraception has a correlation with the risk of obesity.